1984
DOI: 10.1115/1.3239565
|View full text |Cite
|
Sign up to set email alerts
|

A Theory of Rotating Stall of Multistage Axial Compressors: Part I—Small Disturbances

Abstract: An analysis is made of rotating stall in compressors of many stages, finding conditions under which a flow distortion can occur which is steady in a traveling reference frame, even though upstream total and downstream static pressure are constant. In the compressor, a pressure-rise hysteresis is assumed. Flow in entrance and exit ducts yield additional lags. These lags balance to give a formula for stall propagation speed. For small disturbances, it is required that the compressor characteristics be flat in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(51 citation statements)
references
References 0 publications
1
50
0
Order By: Relevance
“…Engineers usually associated the former with a part-span stall which results in a small performance drop, whereas they associate the latter with a full-span stall and a large drop in performance. Notably, the part-span rotating stall occurs typically in single blade rows [6] and usually leads to more complex disturbances in single-rotor or stage machines than in multistage compressors [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineers usually associated the former with a part-span stall which results in a small performance drop, whereas they associate the latter with a full-span stall and a large drop in performance. Notably, the part-span rotating stall occurs typically in single blade rows [6] and usually leads to more complex disturbances in single-rotor or stage machines than in multistage compressors [3].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have studied the detection and analysis of these different forms of aerodynamic instabilities for several decades. Numerous studies have clarified the problem of rotating stall of axial fiow compressors and focus on multistage machines [1][2][3]. The earlier work of Emmons et al [4] was one of the first attempts to describe the mechanism underlying the propagation of rotating stall.…”
Section: Introductionmentioning
confidence: 99%
“…The derivation of (1) and the analysis of transient behaviour including the dynamic pressure rise can be found in [11,12].…”
Section: Compressor Systemmentioning
confidence: 99%
“…Historically, in order to provide a simple yet effective model to predict stability margin of a compressor with inlet distortion, many efforts including various small perturbation theories [1] , parallel compressor models [2] , actuator disk theories [3] , and Moore-Greitzer based inertia parameter models [4][5] have been made. Longley et al [6] studied several multistage low-speed compressors with various RID and concluded that the excitation-and-response theory based on the 2D H-G model matched nicely with the test results of those compressors that exhibited only one peak in the response curve of stall margin shift versus distortion rotation speed, but failed to make a good agreement with those machines which had two peaks in the same kind of response curve.…”
Section: Introductionmentioning
confidence: 99%